PUO with multiple abscesses due to Burkholderia pseudomallei: a case report - Roy, Partha Pratim; Agarwala, Abinash; Sarkar, Samir Kumar; Mandal, Animesh (International Journal of Research in Medical Sciences, 2017)
Melioidosis is an infectious disease of humans and animals caused by Burkholderia pseudomallei, previously called as Pseudomonas pseudomallei. We reported a case of a 14 year old female patient presented with fever for last 3 months and multiple swellings of joints, misdiagnosed as M.D.R. T.B. But after proper evaluation diagnosed as multiple joint abscess due to Pseudomonas pseudomallei mimiking tuberculosis. Sporadic cases of melioidosis from various parts of South Indiaand Western costal India have been reported, but remained underdiagnosed due to lack of awareness.